Effects of alvocidib and carboplatin on ovarian cancer cells in vitro - Baumann, K.H.; Kim, H.; Rinke, J.; Plaum, T.; Wagner, U.; Reinartz, S. (Experimental Oncology, 2013)
Aim: Failure of platinum chemotherapy is an unresolved issue in ovarian cancer. Targeted therapy has been added to the treatment options in solid cancers. Alvocidib is a cyclin dependent kinase inhibitor. Materials and methods: This study evaluated the effects of alvocidib together with carboplatin on ovarian cancer cells (BG-1 and Skov-3) in vitro applying proliferation assays, cell cycle distribution analyses, apoptosis induction assays, and drug accumulation assay. Results: Proliferation of both cell lines was inhibited by carboplatin and alvocidib. The interaction index revealed drug synergism at distinct drug concentrations. Cell cycle distribution was altered. Alvocidib induced apoptosis in Skov-3 cells, and necrosis in BG-1 cells. Rhodamine accumulation was increased by alvocidib or both compounds together. Conclusion: These data provide evidence for antiproliferative effects of alvocidib on human ovarian cancer cells in vitro associated with changes in cell cycle distribution, the induction of apoptosis, and modulation of intracellular drug accumulation. Alvocidib and carboplatin showed some cooperative activity.